Impact of non-thermal variables on hydroxylated GDGT distributions around Iceland - Harning, David J.; Sepúlveda, Julio (Frontiers in Earth Science, 2024)
Archaeal isoprenoid glycerol dibiphytanyl glycerol tetraethers (GDGTs) preserved in sediments are popular tools for the reconstruction of past temperature in the global ocean. Whereas the most common GDGTs have been well studied through environmental and culture studies, their hydroxylated version (OH-GDGTs) is just emerging as a new proxy. Some empirical evidence suggests that the distribution of OH-GDGTs may capture sea surface temperature variability. However, the effects of additional environmental factors on OH-GDGT distributions have not been rigorously tested, and evidence suggests that salinity, sea ice, seasonality, terrestrial input, and water depth may be additional factors in some settings. In this study, we analyzed the distribution of OH-GDGTs in modern and Holocene marine sediment from the North Iceland Shelf. By statistically comparing the biomarker datasets against a collection of modern instrumental and paleoceanographic records, we separated which environmental variables may be controlling OH-GDGT-derived proxies around Iceland. In contrast to prevailing theory, we found that nitrate concentrations and water-column stratification are best correlated to OH-GDGT distributions, and not temperature. These results hold important implications for the application of OH-GDGT proxies in high-latitude oceans, particularly in highly stratified locations, as well as for future studies on the biological sources and functionality of these lipids. Given the current complexity of proxy interpretation, we urge caution in the current application of OH-GDGTs as a tool in paleotemperature reconstructions.